IMPROVING THE FINANCING OF INFRASTRUCTURE PROJECTS BASED ON PUBLIC-PRIVATE PARTNERSHIPS (PPP) (American Journal of Business Management, Economics and Banking, 2026)
This article examines the development, implementation, and key challenges of public–private partnership (PPP) mechanisms in Uzbekistan, with a focus on their role in infrastructure financing and socio-economic development. The study analyzes national legal and institutional frameworks, including the Law on Public–Private Partnership and strategic government programs such as the “Development Strategy of New Uzbekistan 2022–2026” and “Uzbekistan–2030”. It also explores sectoral PPP initiatives in energy, transport, education, healthcare, and water management, highlighting their contribution to improving public services and attracting private investment.The research draws on statistical data from national ministries and international organizations, including the OECD and Asian Development Bank, to assess investment trends, project implementation dynamics, and regional distribution of PPP projects. The findings indicate that while Uzbekistan has made significant progress in expanding PPP practices and attracting foreign and domestic investment, several challenges remain. These include inefficient risk allocation, growing contingent liabilities, delays in user payments, macroeconomic volatility, and regulatory uncertainties.The study concludes that PPPs play a crucial role in addressing infrastructure gaps and enhancing economic efficiency, but their success largely depends on effective governance, transparent institutional mechanisms, and balanced risk-sharing between public and private partners. Strengthening these aspects is essential for ensuring sustainable infrastructure development and long-term economic growth in Uzbekistan.